Covalent bonds enhancing and microstructure evolution induced by carbon content in multi-component (TiZrNbMo)Cx ceramics - Lei Chen; Qingyi Kong; Qinchen Liu; Sijia Huo; Mingxuan Mao; WeiWei Sun; Yujin Wang; Yu Zhou (Journal of Materiomics)
The mechanism underlying the influence of carbon vacancies on the comprehensive properties of multi-component carbide ceramics has been thoroughly investigated. A series of (TiZrNbMo)Cx ceramics with varying carbon content were fabricated using spark plasma sintering (SPS). Detailed examinations were conducted on the phase composition, microstructure evolution, as well as mechanical and thermal properties, in response to carbon content variation. The variations in bonding states and charge distribution were calculated to elucidate the mechanism through the influence of carbon vacancies. The observed nano hardness peak of (33.3 ± 0.4) GPa in the C0.75-22 sample is attributed to the enhanced strength of the M−C covalent bond induced by the presence of carbon vacancies. Moreover, the exceptional lattice stability and resistance to compression were further validated through theoretical simulations of compression deformation performed via ab initio molecular dynamics (AIMD). Additionally, the presence of carbon vacancies was found to enhance the phonon and electron scattering, and thus led to reduce the thermal conductivities.